2012
DOI: 10.1038/ejcn.2012.68
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coffee consumption on serum lipids: a meta-analysis of randomized controlled trials

Abstract: BACKGROUND/OBJECTIVES: Numbers of epidemiological studies assessing coffee consumption and serum lipids have yielded inconsistent results. We aimed to evaluate the effects of coffee intake on serum lipids. SUBJECTS/METHODS: We searched several English and Chinese electronic databases up to September 2011 for randomized controlled trials of coffee on serum lipids. Weighted mean effect size was calculated for net changes in serum lipids by using random-effect models or fixed-effect models. Subgroup and meta-regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
129
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 34 publications
15
129
2
9
Order By: Relevance
“…Instant coffee and ground bean coffee manufacturing methods differ; therefore, differences 206 in ingredient composition and content after coffee extraction may exist. In previous studies, filtered 207 coffee had different physiological effects than boiled coffee by filtering of lipophilic substances 208 [25,37]. Further studies are warranted to identify residual confounding factors.…”
mentioning
confidence: 96%
“…Instant coffee and ground bean coffee manufacturing methods differ; therefore, differences 206 in ingredient composition and content after coffee extraction may exist. In previous studies, filtered 207 coffee had different physiological effects than boiled coffee by filtering of lipophilic substances 208 [25,37]. Further studies are warranted to identify residual confounding factors.…”
mentioning
confidence: 96%
“…These compounds and coffee drinking are positively correlated with higher level of serum cholesterol lipids, especially in patients with hyperlipidemia [81,82]. Latest research showed that they reduce the risk of colorectal cancer [83].…”
Section: Determination Of Diterpenesmentioning
confidence: 99%
“…The cardiovascular effects of coffee drinking depend in part on coffee preparation method and individual characteristics (eg, hypertension and hyperlipidemia). [1][2][3] There are 2 main methods of coffee preparation: filtered and unfiltered. Filtered coffee, also known as drip-brewed coffee, is the most common mode of preparation in the United States and involves brewing the coffee through a paper filter.…”
Section: Coffeementioning
confidence: 99%